1996
DOI: 10.1073/pnas.93.24.14047
|View full text |Cite
|
Sign up to set email alerts
|

Tumor progression to the metastatic state involves structural modifications in DNA markedly different from those associated with primary tumor formation

Abstract: Wavenumber-absorbance relationships of infrared spectra of DNA analyzed by principal components analysis may be expressed as points in space. Each point represents a highly discriminating measure of DNA structure. Structural modifications of DNA, such as those induced by free radicals, alter vibrational and rotational motion and consequently change the spatial location of the points. Using this technology to analyze breast tumor DNA, we revealed a 94؇ difference in direction between the progression of normal D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
34
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 28 publications
4
34
0
Order By: Relevance
“…In an attempt to answer this question, we used Fourier transform-infrared (FT-IR) spectroscopy with multivariate statistics to delineate structural differences between thin films of a 25-base DNA strand and comparable strands containing centrally located single G o and A o groups. FT-IR͞statistical analysis was previously used to study subtle changes in base and phospho-deoxyribose structures of DNA in relation to tumor progression (13)(14)(15)(16)(17)(18)(19). In the present study, a number of spectral differences attributable to base interactions and backbone conformations were identified between the 25-base parent strand and derivatives containing G o and A o substituents.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…In an attempt to answer this question, we used Fourier transform-infrared (FT-IR) spectroscopy with multivariate statistics to delineate structural differences between thin films of a 25-base DNA strand and comparable strands containing centrally located single G o and A o groups. FT-IR͞statistical analysis was previously used to study subtle changes in base and phospho-deoxyribose structures of DNA in relation to tumor progression (13)(14)(15)(16)(17)(18)(19). In the present study, a number of spectral differences attributable to base interactions and backbone conformations were identified between the 25-base parent strand and derivatives containing G o and A o substituents.…”
mentioning
confidence: 82%
“…In this regard, FT-IR spectroscopy with multivariate statistics is known to be sensitive to subtle changes in the base and backbone structures of DNA in cancer-prone tissues and neoplasms [e.g., prostate (15) and breast (14,18,19)]. The FT-IR͞statistical approach is thus an attractive means for acquiring information on conformational and other changes in a variety of synthetic and natural DNA structures (17).…”
Section: Discussionmentioning
confidence: 99%
“…Results and Discussion MCA-Induced DNA Damage Before Tumor Formation. We have demonstrated that the FTIR statistical models of DNA used in this study are capable of identifying a variety of subtle changes in base functional group and backbone structures as well as alterations in conformational properties (20) associated with carcinogenesis (19,21,(23)(24)(25). Specifically, this technology has been used most recently to discriminate between DNA structures of normal prostate tissues, primary tumors, metastasizing primary tumors, and distant metastases of the prostate (18).…”
Section: Methodsmentioning
confidence: 99%
“…These structural changes have been found in various stages of primary and metastatic tumor development (10)(11)(12)(13)(14)(15). In a recent study (16), the FTIR technology effectively differentiated between the prostate DNA of histologically normal tissues, nonmetastasizing primary tumors, metastasizing primary tumors, and distant metastases of prostatic carcinomas.…”
mentioning
confidence: 99%